Sizing the Protein Translocation Pathway of Colicin Ia Channels - Kienker, Paul K. (The Rockefeller University Press, 2003)
The bacterial toxin colicin Ia forms voltage-gated channels in planar lipid bilayers. The toxin consists of three domains, with the carboxy-terminal domain (C-domain) responsible for channel formation. The C-domain contributes four membrane-spanning segments and a 68-residue translocated segment to the open channel, whereas the upstream domains and the amino-terminal end of the C-domain stay on the cis side of the membrane. The isolated C-domain, lacking the two upstream domains, also forms channels; however, the amino terminus and one of the normally membrane-spanning segments can move across the membrane. (This can be observed as a drop in single-channel conductance.) In longer carboxy-terminal fragments of colicin Ia that include ≤169 residues upstream from the C-domain, the entire upstream region is translocated. Presumably, a portion of the C-domain creates a pathway for the polar upstream region to move through the membrane. To determine the size of this translocation pathway, we have attached “molecular stoppers,” small disulfide-bonded polypeptides, to the amino terminus of the C-domain, and determined whether they could be translocated. We have found that the translocation rate is strongly voltage dependent, and that at voltages ≥90 mV, even a 26-Å stopper is translocated. Upon reduction of their disulfide bonds, all of the stoppers are easily translocated, indicating that it is the folded structure, rather than some aspect of the primary sequence, that slows translocation of the stoppers. Thus, the pathway for translocation is ≥26 Å in diameter, or can stretch to this value. This is large enough for an α-helical hairpin to fit through.